Unraveling Shengmuxiang in Jiang-flavor base baijiu using a combination of metabolomics and sensomics strategy - Yang Xu; Lizhang Yang; Yubo Yang; Fan Yang (Food Chemistry: X, 2024)
Shengmuxiang (SMX), an important aroma in Jiang-flavor base baijiu, significantly influences the quality of the product. This study employed untargeted metabolomics combined with sensomics to explore the key compounds responsible for SMX. Results indicated that SMX samples had higher intensities of green and woody-like odors compare to control samples. A total of 87 aroma compounds were identified by headspace solid phase microextraction combined with gas chromatography–mass spectrometry technology. Based on the variable projection importance, PCA and OPLS-DA were employed to identify 22 potential marker compounds. Quantitative results combined with hierarchical cluster and OAV analysis revealed that 9 aroma compounds (OAV > 1) had high concentrations in SMX samples. Aroma recombination and omission experiments further indicated that acetaldehyde and acetal were the key compounds responsible for the characteristic aroma of SMX in Jiang-flavor base baijiu. These findings provide valuable insights into the distinct aroma profile of SMX and offer a basis for quality control of Jiang-flavor base baijiu.